Performing trauma in Central Africa - Edmondson, Laura, 1970- (Bloomington, Indiana)
xv, [1] sayfa harita, 348 sayfa
Keywords: “What are the stakes of cultural production in a time of war? How is artistic expression prone to manipulation by the state and international humanitarian organizations? In the charged political terrain of post-genocide Rwanda, post-civil war Uganda, and recent violence in the Democratic Republic of Congo, Laura Edmondson explores performance through the lens of empire. Instead of celebrating theatre productions as expression of cultural agency and resilience, Edmondson traces their humanitarian imperatives to a place where global narratives of violence take precedence over local traditions and audiences. Working at the intersection of performance and trauma, Edmondson reveals how artists and cultural workers manipulate narratives in the shadow of empire and how empire, in turn, infiltrates creative capacities“ -- Yayıncı.